Postindustrial possibilities : a critique of economic discourse - Block, Fred L. (University of California Press, 1990)
While it is often acknowledged that we live in a "postindustrial" age, our economic concepts have lagged far behind our postmodern sensibility. In this incisive new work, the well-known sociologist, Fred Block, sheds obsolete and shopworn economic analysi
Keywords: Economic forecasting.; Prévision économique.; BUSINESS & ECONOMICS -- Economics -- Theory.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Economic forecasting